La vinculación Fonológica- Grafica en el proceso de aprendizaje de Lengua y Literatura en los Estudiantes de Segundo año de Educación Básica de la Unidad Educativa “Cotaló” - Guamán Rodríguez, Mery Alicia (2022)
This research was carried out with the objective of developing the skills of phonological - graphic linkage in the learning process of Language and Literature in second year E.G.B. students, which will contribute to the formation of children through the combination of speaking, listening and writing. To fulfill the purpose of the research, theoretical foundations related to the learning process of Language and Literature and graphic phonological skills were determined. The research was carried out under the quantitative and qualitative approach, the descriptive and correlational level of a transversal nature was used, which allowed collecting the information required to analyze and describe the data, aimed at responding to the problem posed. The technique used was interview and observation through an interview guide and an observation sheet, respectively; which were applied to 38 Second Year E.G.B. belonging to the Elementary Basic Education level of the Cotaló Educational Unit, three classroom teachers and the institution's rector. The results obtained showed that there is a 44.74% of students who have problems in the development of phonological - graphic skills and abilities, since the students alter the phonemes when speaking and writing. In order to solve the problem, a Didactic Guide was designed for the phonological and graphic link that will allow to reinforce the learning of Language and Literature in the second year students of E.B.G.